Relationship Between Emotional Maturity And Self-Esteem In Adolescents At The Orphanage - Leony Rahmawati; Ratriana Yuliastuti Endang Kusumiati (G-Couns: Jurnal Bimbingan dan Konseling, 2024)
Adolescence is often called a period of rebellion, because of emotional turmoil, withdrawal, and various problems in various environments. Emotional maturity influences a teenager's development, helping them manage their emotions and increase their self-esteem. This research examines the relationship between emotional maturity and self-esteem in adolescents at the Salatiga orphanage. The method used was quantitative with a correlational analysis design with 150 participants from 5 nursing homes in Salatiga using random sampling techniques. The measuring instruments used were the Emotional Maturity Scale (EMS)(α = 0.75) and the self-liking and self-competence questionnaires (SLCS) scale (α = 0.94). The data analysis method uses the product moment correlation test from Karl Pearson. The hypothesis test results of the Pearson correlation value are -0.243 with a significance value = 0.001 (p < 0.05). The results show a significant negative relationship between emotional maturity and self-esteem in adolescents at the Salatiga orphanage. Keywords: emotional maturity, pride, adolescent, orphanage